Dilema Prioritas Nafkah Generasi Sandwich: Analisis Fiqh Kritis Berbasis Kaidah Al-Farḍu Afḍalu Mina An- Nafli Dan Al-Wājib Lā Yutrak Illā Liwājibin - Nabiilatun Najmah (Pusat Riset dan Inovasi Nasional, 2026)
The phenomenon of the “Sandwich Generation” (SG) in Indonesia, where individuals of productive age (30-40 years old) bear a double financial burden—supporting the needs of their children and immediate family (furu') while also supporting their elderly parents (ushul)—has become a widespread social and financial challenge. This pressure, exacerbated by inadequate income and low financial literacy, forces 94% of SG respondents to set aside their personal interests. This dilemma calls for a clear Sharia analysis of the priority scale of financial support. This article aims to analyze the SG maintenance dilemma through the Qawa'id Fiqhiyyah (Fiqh Principles) framework to establish a hierarchy of financial obligations. The two main principles used are Al-Farḍu afḍalu mina an-Nafli (Absolute Obligation takes precedence over Sunnah) and Al-Wājib lā yutrak illā liwājibin (An Obligation cannot be abandoned except for another Obligation). Fiqh analysis shows that the resolution of priority conflicts is based on the classification of the legal status of the recipient of alms, distinguishing between absolute obligations (Adami rights, contractual) and conditional obligations (wajib zhanni, Allah's rights). Key findings establish Sharia priorities in conditions of limitation: Self, Wife and Children (Absolute Obligations), Parents (Conditional Obligations), Siblings/Relatives (Sunnah/Nafl). This priority is established to protect the nuclear family unit as the foundation of society, in line with Maqāṣid ash-Sharīʿah (Sharia Objectives).